Study of Mohr-Coulomb Parameters in Clay Soil with the Addition of PCC Cement (Portland Cement Composite) and Lime (CAO) Under PassiveConfinement of GFRP (Glass Fiber Reinforced Polymer) - Ayu Dewadatta, Ni Wayan Amrita; Lestari, Laras Laila; Piscesa, Bambang; Sutrisno, Wahyuniarsih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to analyze the physical and mechanical behavior of soil stabilized with the addition of PCC cement and lime (CaO) as well as the application of passive confinement using a polymer layer reinforced with glass fiber (GFRP). Soil stabilization was carried out by mixing 8% cement and 4% lime based on the optimum mix design results. Soil specimens were compacted using the standard compaction method and tested at 28 days of age. Next, the test specimens were coated with 1, 2, and 3 layers of GFRP to examine the passive effect on compressive strength. The test results show that the addition of PCC cement and lime (CaO) can significantly increase soil strength. Mohr-Coulomb analysis shows cohesion values of 0.032 MPa; 0.046 MPa; and 0.115 MPa, as well as shear angles of 45.46°, 45.08°, and 44.99° for each number of GFRP layers. The application of GFRP as a passive restraint also provides a gradual increase in compressive strength according to the number of layers used. This study proves that the combination of soil stabilization using PCC cement, lime, and the gradual application of GFRP is effective in improving the physical and mechanical properties of the soil, particularly for construction needs that require high load-bearing capacity.